2013
DOI: 10.1371/journal.pone.0068842
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an Association between CYP11B2 C-344T Gene Polymorphism and Ischemic Stroke: A Meta-Analysis of 7,710 Subjects

Abstract: BackgroundThe association between aldosterone synthase (CYP11B2) C-344T gene polymorphism and ischemic stroke remains controversial and ambiguous. To better explain the association between CYP11B2 polymorphism and ischemic stroke risk, a meta-analysis was performed.MethodsBased on comprehensive searches of Medline, Embase, Web of Science, CNKI and CBM databases, we identified and abstracted outcome data from all articles to evaluate the association between CYP11B2 polymorphism and ischemic stroke. The pooled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Variants in several genes were identified as risk factors for IS, including apolipoprotein B , beta-2 adrenergic receptor , methylenetetrahydrofolate reductase ( MTHFR), and HDAC9 [4953]. However, some other variants, such as IL-6 G572C, PON1 L55M, and CYP11B2 C-344T were not associated with susceptibility to IS [44,54,55]. Thus, we saw the need to perform a meta-analysis aimed to investigate the contribution of SNP56 in the PDE4D gene to IS.…”
Section: Discussionmentioning
confidence: 99%
“…Variants in several genes were identified as risk factors for IS, including apolipoprotein B , beta-2 adrenergic receptor , methylenetetrahydrofolate reductase ( MTHFR), and HDAC9 [4953]. However, some other variants, such as IL-6 G572C, PON1 L55M, and CYP11B2 C-344T were not associated with susceptibility to IS [44,54,55]. Thus, we saw the need to perform a meta-analysis aimed to investigate the contribution of SNP56 in the PDE4D gene to IS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ] In contrast, Pi et al . [ 48 ] conducted a meta-analysis in 2013 to investigate genetic susceptibility to ischemic stroke using the 344C/T polymorphism of the CYP11B2 gene, and their results did not find any relationship between the two. [ 48 ]…”
Section: R Esultsmentioning
confidence: 99%
“…concluded that the homogeneous T allele of the –344C/T polymorphism of the CYP11B2 gene was a marker of the risk of developing hypertension but was not associated with vascular changes in hypertension. [ 43 , 48 ]…”
Section: R Esultsmentioning
confidence: 99%
“…However, there have been some studies, the results of which did not reveal the association of CYP11B2 gene polymorphisms with the development of cardiovascular diseases [33][34][35][36][37].…”
Section: Type I Angiotensin Ii Receptor (Agtr1)mentioning
confidence: 99%